PENGARUH COUNTRY IMAGE TERHADAP KEPUTUSAN PEBELIAN ETUDE HOUSE DI SEMARANG MELALUI BRAND IMAGE SEBAGAI VARIABEL INTERVENING - Aliya Larassati Indraputri; Dina Lestari (Jurnal Ilmu Administrasi Bisnis, 2019)
This study aims to examined the effects of country image (general country attitudes and general product attitudes) to purchase intention through brand image. The population of this research is consumers of Etude House in Semarang, while the sample is 100 consumers of Etude House with some certain prerequirements. The data was analyzed using multiple linear regression analysis with SPSS 21.0 for windows and sobel test used to test the influence of mediation from intervening variable. The result of this study is showing that country image (general country attitudes and general product attitudes) has positive impact toward brand image, the biggest impact is own by general product attitudes. The test results of the influence of mediation, brand image can madiate the effect of general country attitudes (gca) on purchase intention significantly and can be mentioned as a partial mediation variable, and also brand image can madiate the effect of general product attitudes (gpa) on purchase intention significantly and can be mentioned as a partial mediation variable.